Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.

Multi-step continuous flow synthesis of the cystic fibrosis medicine ivacaftor - Vasudevan, N.; Sharma, Mrityunjay K.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2018)
A continuous flow ozonolysis method combined with a multi-step flow sequence is developed for the synthesis of the drug ivacaftor for the first time. Safe ozonolysis, a continuous flow quadruple reaction to construct a quinolone scaffold, and inline extraction followed by continuous phase separation are the key features of the present work. The feasibility of using a continuous mixed flow reactor, commonly referred to as a continuous stirred tank reactor (CSTR), is also investigated for the relatively slow reaction step. The current integrated multi-step flow synthesis can produce 7.2 g of the drug ivacaftor per day on a laboratory scale, which is sufficient to treat 50 patients per day. The present route can also be used as a general route for the synthesis of other related drugs such as quinolone antibiotics.